1997
DOI: 10.1103/physrevlett.79.483
|View full text |Cite
|
Sign up to set email alerts
|

Universal Heat Conduction inYBa2Cu3O6.9

Abstract: The thermal conductivity of YBa2Cu3O6.9 was measured at low temperatures in untwinned single crystals with concentrations of Zn impurities from 0 to 3% of Cu. A linear term κ0/T = 0.19 mW K −2 cm −1 is clearly resolved as T → 0, and found to be virtually independent of Zn concentration. The existence of this residual normal fluid strongly validates the basic theory of transport in unconventional superconductors. Moreover, the observed universal behavior is in quantitative agreement with calculations for a gap … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
220
4

Year Published

2001
2001
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(248 citation statements)
references
References 20 publications
24
220
4
Order By: Relevance
“…Moreover, as expected for the case of a d-wave gap [6,7], the amplitude of this term was found to be universal; i.e. independent of impurity concentration [5]. Recently, Durst and Lee [3] showed that, regardless of Fermi-liquid corrections, this amplitude is intimately related to the fine structure of the superconducting gap in the vicinity of the nodes.…”
mentioning
confidence: 80%
“…Moreover, as expected for the case of a d-wave gap [6,7], the amplitude of this term was found to be universal; i.e. independent of impurity concentration [5]. Recently, Durst and Lee [3] showed that, regardless of Fermi-liquid corrections, this amplitude is intimately related to the fine structure of the superconducting gap in the vicinity of the nodes.…”
mentioning
confidence: 80%
“…One drawback is the need to separate phonon and electron contributions, but in the cuprate superconductors an asymptotic linear term, κ 0 /T ∼ const which can be attributed solely to quasiparticles is almost always present at the lowest temperatures. After theoretical predictions of the universality of low-T quasiparticle transport in nodal superconductors [1], experimental confirmation was obtained in a number of optimally doped materials [2]. According to the theory, which relies on the disorder-averaged self-consistent T -matrix approximation (SCTMA), the low-T thermal conductivity is given by…”
Section: Introductionmentioning
confidence: 99%
“…The presence of line nodes is further supported by a finite κ 00 /T term in zero field. For line nodes, κ 00 /T is given by κ00 T ≃ L0 ρ0 · ξ ab ℓe , where ξ ab and ℓ e are the coherence length and mean free path within the ab-plane, respectively [19]. To estimate ξ ab , we use H s instead of H c c2 , assuming the line nodes in the smaller gap.…”
mentioning
confidence: 99%